2017
DOI: 10.5430/jer.v3n1p51
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CTX-M beta-Lactamases in Escherichia coli from community-acquired urinary tract infections and associated risk factors among women in Cameroon

Abstract: Background: In recent years, a worldwide dissemination of CTX-M beta-lactamase-type in Escherichia coli strains isolates from community-acquired urinary tract infections (CA-UTI) has been observed. However little is known on the prevalence and risk factors of this global threat in developing countries. Objective: The aim of this study was to study the prevalence and risk factors for CA-UTI in Yaoundé, Cameroon. Methods: Eighty six patients with urinary E.coli infection recruited from 10 health structures in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…Similar finding has already been reported that all strains of E. coli had CTX-M gene [21]. It has also been documented that clinical isolates of E. coli and Klebsiella spp.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar finding has already been reported that all strains of E. coli had CTX-M gene [21]. It has also been documented that clinical isolates of E. coli and Klebsiella spp.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the period of hospitalization, hygienic conditions and drinking water quality also propagate MDR microbes as it has been reported that short-time stay of burn patients in hospital (7 days) led to 10% colonization of microbes while longtime stay (50 days) increased colonization up to 90% [35]. Another study reported that poor hygienic conditions such as contaminated drinking water promote Enterobacteriaceae strains circulation leading to MDR [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, more than half of urine samples were positive to E. coli and 23 E. coli O157 isolates were obtained. Previous studies conducted in various parts of the world showed that the prevalence rate of E. coli O157 was about 10% [21,22]. In this study, the contamination rates were only approximate values.…”
Section: Discussionmentioning
confidence: 69%